2020
DOI: 10.1039/c9nj06358g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of micro–mesoporous CPO-27-Mg@KIT-6 composites and their test in CO2 adsorption

Abstract: Novel composites were synthesised through a fusion between CPO-27-Mg framework and mesoporous silica KIT-6 and tested in the CO2 adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…The EDX images of the supported ILs are exhibited in Figure 3, in which the corresponding elemental signals were distributed homogeneously and consistently, indicating the successful formation of the supported ILs species as well. Similar results are obtained by UV-Vis characterization (Figure 4), the intensity of diffraction peak at around 223 nm is attributed to Si-O species of KIT-6 [48][49][50]. Obviously, after immobilization of ionic liquids, no significant peaks attributed to the ionic liquids particles are found in the UV-Vis patterns, which may be owing to the well-dispersed ionic liquids particles encapsulated in mesoporous channels of the KIT-6 support.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The EDX images of the supported ILs are exhibited in Figure 3, in which the corresponding elemental signals were distributed homogeneously and consistently, indicating the successful formation of the supported ILs species as well. Similar results are obtained by UV-Vis characterization (Figure 4), the intensity of diffraction peak at around 223 nm is attributed to Si-O species of KIT-6 [48][49][50]. Obviously, after immobilization of ionic liquids, no significant peaks attributed to the ionic liquids particles are found in the UV-Vis patterns, which may be owing to the well-dispersed ionic liquids particles encapsulated in mesoporous channels of the KIT-6 support.…”
Section: Resultssupporting
confidence: 84%
“…After the immobilization of ionic liquid on the KIT-6 support, the typical aggregated small spherical particles can be seen in the beta zeolite, and the particles which are aggregated into big block constitute the Beta seed. The SEM images of KIT-6 and KIT-6 supported ionic liquids indicated that both of them have irregular particle morphologies, which are almost identical to the literature [48][49][50]. The EDX images of the supported ILs are exhibited in Figure 3, in which the corresponding elemental signals were distributed homogeneously and consistently, indicating the successful formation of the supported ILs species as well.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations